Production of biodiesel through transesterification of sunflower oil using SiO2/50% H2SO4 solid acidic catalyst - Tan, Inn Shi (2010)
A renewable fuel such as biodiesel, with lesser exhaust emissions, is the need of the day. Hence, researchers and scientific community worldwide have focused on development of biodiesel and the optimization of the processes to meet the standards and specifications needed for the fuel to be used commercially without compromising on the durability of engine parts. Based on the intricacies associated with the homogeneously catalyzed transesterification process, the purpose of the present work is to study biodiesel production by transesterification of sunflower oil with methanol in a heterogeneous system, using silica gel loaded with sulfuric acid (SiO2/50%H2SO4) as a solid acidic catalyst. The catalyst prepared by loading of 50v/v% H2SO4 on silica gel followed by drying it at 110°C. The catalysts were characterized by FTIR, TGA and SEM. The reaction between sunflower oil and methanol is carried out in a 3-necked round bottom flask heated by a rotamantle. The sample is withdrawn at certain time interval and is analyzed using gas chromatography. The dependence of the conversion of sunflower oil on the reaction variables such as the molar ratio of methanol to oil, reaction temperature and catalyst loading was studied. The catalyst has exhibited maximum oil conversion (84wt.%) under the conditions of 100°C, methanol/oil molar ratio of 6:1 and catalyst amount 10%. Kinetic study of reaction was also done. The experimental data is well fitted to the Pseudo-homogeneous model. This optimum operating condition and kinetic model are very important for producing biodiesel fuel effectively in a larger scale.